Planeación en la educación superior: La experiencia de la Universidad EAFIT 1997 - 2003 (2004)
Planning in higher education is an important process for the development of these types of institutions. This article show the experience of EAFIT University in this aspect, during the period of 1997 to 2003, through the presentation and evaluation of the currently used focus and planning system; the revision of objectives, the strategies, and the obtained results, and the consideration of the main problems to be faced and the main perspectives of the university in this aspect.